The essential work of fracture and JR curves for the double cantilever beam specimen : an examination of elastoplastic crack propagation - Atkins, A. G. (2012)
The propagation of a crack in a double-cantilever beam (DCB) geometry where there is extensive remote plastic flow both preceding and accompanying fracture is analysed. Experiments show that there is an appreciable path dependence in load-deflection-crack length behaviour because of the remote residual plastic zones left in the wake of the crack front. The deflection for a propagated crack is greater than the deflection predicted by nonlinear fracture mechanics since in real plasticity the plastic deformations cannot be recovered and their ‘energy’ released back into the system. A Griffith energy approach is employed to uncouple the work increments of elastic strain energy, the remote plastic work and the essential crack-tip fracture work. For geometries other than the DCB these components cannot be easily uncoupled. Analyses are given for elastic perfectly plastic solids and for elastic power-law work-hardening materials. There is good agreement with experiments on side-grooved double cantilever beam specimens made from 6082-TF aluminium alloy (which is almost elastic perfectly plastic) and from annealed α-brass (which work hardens appreciably). Varying degrees of elastoplasticity during propagation are obtained by altering the height of the beam arms; globally elastic fracture results are obtained with adequately deep arms.